PENERAPAN METODE PERMUKAAN RESPONS DALAM MASALAH OPTIMALISASI - DEWI, ADE KUSUMA; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2013)
The experiments were conducted to determine the relationship between response variable and independent variable and the effect of independent variables to response variable. Multiple comparison tests can be used to find the level that makes optimal response. However, this test has a drawback that it only finds the optimal level tested at the level being considered. Thus test is more suitable for qualitative independent variables. On the other hand, for quantitative independent variables we can use the orthogonal polynomial method and response surface method (RSM).The purpose of this research is to apply RSM to produce optimal response. It can be concluded that RSM is an efficient used to find the level of independent variables to makes optimal response.
Keywords: Experiments Design; Response Surface Method